Mapping the Word Reading Circuitry in Skilled and Disabled Readers - Pugh, K.R.; Frost, S.J.; Sandak, R.; Landi, N.; Moore, D.; Porta, G.D.; Rueckl, J.G.; Einar Mencl, W. (The Neural Basis of Read., 2010)
This chapter describes recent studies designed to generate data not only on the localization of reading-related brain activation, but also to examine patterns of interactions and dynamic trade-offs among these distributed reading-related systems. It begins with a review of relevant behavioral studies of component processing in fluent reading, with particular emphasis on the role of early (sublexical) phonology. It then discusses the current literature on the neurobiology of skilled and disabled reading, along with consideration of a series of recent studies that aim to capture brain correlates of component processing, again with an emphasis on phonological processing, adaptive learning, and complex trade-offs and interactions. Finally, it takes stock of what is considered to be crucial next steps (both technical and theoretical) in the emerging cognitive neuroscience of reading and its disorders. © Oxford University Press, 2014.
Keywords: Neurobiology; Reading disability; Reading systems; Skilled reading; dept.sed

Patterns of reading disabilities across development - Spear-Swerling, L. (Handbook of Reading Disability Research, 2010)
Keywords: dept.sed

Assistive technology - Newton, Deborah A.; Dell, Amy G. (Journal of Special Education Technology, 2010)
Keywords: dept.sed

Assistive technology - Newton, Deborah A.; Dell, Amy G. (Journal of Special Education Technology, 2010)
Keywords: dept.sed

Relationships between sixth-graders' reading comprehension and two different measures of print exposure. - Spear-Swerling, Louise; Brucker, Pamela; Alfano, Michael (Reading and Writing, 2010)
This study examined sixth-graders' reading comprehension and component reading abilities in relation to two measures of print exposure: an author recognition test (ART) involving fiction authors and a reading habits questionnaire (RHQ) about children's voluntary reading for enjoyment across various genres. The ART correlated only with children's fiction book reading habits, not with other habits such as nonfiction book or magazine reading, and had a stronger relationship to all tested reading abilities than did the RHQ. Strong comprehenders in reading outperformed weak comprehenders on all component reading measures, ART score, and fiction habits; however, weak comprehenders scored higher than did strong comprehenders on the indicator of nonfiction reading habits. The two groups of comprehenders did not differ significantly on other reported reading habits. The results are discussed in relation to children's specific book choices and demonstrate the relevance of genre to evaluations of children's print exposure., (C)2010 Kluwer Academic Publishers
Keywords: Author recognition tests; Print exposure; Reading; Reading comprehension; Reading habits; dept.sed; peer-reviewed